2019
DOI: 10.35690/978-2-7592-2920-8
|View full text |Cite
|
Sign up to set email alerts
|

Systèmes agraires et changement climatique au Sud

Abstract: Stratégies des filières fromagères sous AOP en Europe Modes de régulation et performance économique P. Jeanneaux 2018 Services écosystémiques et protection des sols Analyses juridiques et éclairages agronomiques C. Hermon, coord. 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These findings are in line with many studies in Benin (Loko et al 2012), Niger (Assoumana et al 2016), Nigeria (Mustapha et al 2012 and Kenya (Gebreeyesus, 2017). Similar type of study has been conducted in Tanzania and Senegal has been reported (Cochet et al 2017). But this result is contradictory with the study done by Fosu-Mensah (2010) where only a few farmers have developed adaptation strategies.…”
Section: Farmers' Perceptions Of An Adaptation Strategies To Climate supporting
confidence: 79%
See 1 more Smart Citation
“…These findings are in line with many studies in Benin (Loko et al 2012), Niger (Assoumana et al 2016), Nigeria (Mustapha et al 2012 and Kenya (Gebreeyesus, 2017). Similar type of study has been conducted in Tanzania and Senegal has been reported (Cochet et al 2017). But this result is contradictory with the study done by Fosu-Mensah (2010) where only a few farmers have developed adaptation strategies.…”
Section: Farmers' Perceptions Of An Adaptation Strategies To Climate supporting
confidence: 79%
“…This study indicated that the farmers of the KBNP surrounding areas are well aware of the climate change perception and its impacts on the agricultural production. This study also highlighted that their family also has the perception regarding the climate change (Cochet et al 2017). For implementation of proper policies, adequate knowledge and understanding of risks are very important (Juana et al 2013).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 80%